(untitled) (Indian Journal of Animal Production and Management, 2025)
A study was conducted to understand consumer perception towards meat and meat products consumption in Tirupati city. The city of Tirupati has witnessed a sharp rise in the households which is evident with the rapid expansion of the city outskirts by means of real-estate developments. This pose a greater scope for meat startups to be established in the rapidly developing city. A total of 200 respondents were randomly selected and were interviewed. Data were collected using pre- tested structured interview schedule by personal interviews. The study group comprised of 76 males & 124 females. The educational background of respondents was found to vary between uneducated to PG & PhD level. The overall mean age of the consumers was found to be (33.5) of which majority (45%) belong to middle age group. The study revealed that most of the consumers ate meat for taste (67%) and health benefits (33%) and usually consume meat twice in a week (51%). The most preferred meat was chicken (53%), followed by chevon (21%), sea foods (fish, prawns 16%) and other meat (10%). Gravy type meat products were most preferred, followed by biryani (19%) and fried meat products (15%). Most of the consumers (63%) opined that meat have good cholesterol (HDL) and (28%) as bad cholesterol (LDL) whereas (9%) opined as both. The willingness to purchase chilled/ frozen meat was very low (5%). The acceptance of the respondents towards processed meat products such as pickles (80%), comminuted meat products at (20%) respectively. The majority of the respondents (82%) believed that over consuming of meat leads to heart problems and other diseases. Unfortunately (78%) of the respondents have no idea about what kind of vitamins and minerals are present in meat. Most of the consumers said that ideal method for cooking is boiling (78%) and frying (22%). Only (40%) of the respondents have awareness about zoonotic diseases. Food safety has emerged as an important global issue with international trade and public health implications. The current study also revealed that most of the respondents have no idea about laws pertaining to food safety. The. results indicated that most respondents consume meat for taste and as a cultural tradition. However, majority of the consumers lack scientific backdrop about fresh meat and processed meat, which further can be overcome by conducting extensive awareness programmes and advertisements by the government agencies and entrepreneurs in the meat trade. The consumer awareness about scientific handling of meat can safeguard their health and also pave a way for huge investments in the meat startups in the developing cities.